A putative upupiform bird from the Early Oligocene of the Central Western Carpathians and a review of fossil birds unearthed in Slovakia. (24th October 2013) - Kundrát, Martin; Soták, Ján; Ahlberg, Per E.
Abstract An isolated hind limb of a miniature bird from an Early Oligocene locality (30–34 Ma) near Bystré (Slovakia) is described and analyzed. The tarsometatarsus (TMT) of the specimen is remarkably short relative to the tibiotarsus. When relative length ratios of the bones are compared with a sample of 29 extant and extinct birds with short metatarsi, the specimen variably clusters with some alcedinids, coraciids and trochilids. Log‐clusters give less ambiguous results and indicate significant proximity of the Bystré specimen to the extinct messelirrisorids (Upupiformes) and the recent acledinids (Coraciiformes). With regard to morphological details, such as those of the first metatarsal, II‐IV metatarsal trochleae, intertrochlear incisurae and phalanges, the Slovak specimen shows a combination of features, which are distributed among recent upupiforms and coraciiforms as well as extinct upupiforms (Messelirrisor) and apodiforms (Eocypselus, Parargornis). Taken together, the metric and morphological data sets suggest that the specimen from Bystré is a coraciiform sensu lato rather than an apodiform bird. Within the Coraciiformes, the robust trochlea of MT‐I with expanded dorsal shelf, the large medial and slit‐like lateral intertrochlear incisura, and the long hindtoe suggest upupiform rather than alcedinid relationships.